FINANCIAL INTEGRATION AND ECONOMIC GROWTH IN THE EUROPEAN TRANSITION ECONOMIES - Mirdala, Rajmund (Journal of Advanced Studies in Finance, 2011)
Economic crisis affected economic activity in the European transition economies (ETE) with an unprecedented extent that may be compared to an initial shock ETE experienced at the beginning of the transition process in the early 1990s. Deterioration of the overall macroeconomic performance was followed by the various spurious effects leading to the slowdown in the process of convergence toward Western European countries. One of the key aspects of this long-term trend - participation of ETE in the process of international capital flows became affected by the economic crisis too. While the overall benefits from the cross-border capital movements significantly contributed to the high rates of real output growth in ETE (most of the countries from this group became large net debtors in the last two decades) during pre-crisis period, sudden shift in a direction as well as a size of a foreign capital inflows may markedly affect the speed of the recovery process from the economic crisis. In the paper we observe main trends in the process of an international financial integration in ten ETE since 1995. To estimate effects of foreign capital inflows on the performance of ETE we analyze effects of foreign direct investments, portfolio investments and other investments on the real output development. To meet this objective we estimate vector error correction (VEC) model. We estimate two models (one with data sets for precrisis period only and second for the whole period). To identify structural shocks we implement a Cholesky decomposition of innovations. Impulse-response functions are computed to estimate short-run effects of foreign capital inflows on real output. Compared results for both models should help us to assess the effects of economic crisis. Mutual short-run (temporal) effects of foreign capital inflows on the real output are estimated using linear Granger causality test.